Perbedaan Reaksi Pasar atas Peristiwa Stock Split dan Reverse Stock Split - Artama, Nyoman Suta; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2018)
The purpose of this study is to analyze market reaction on stock split and reverse stock split by using abnormal return and trading volume activity. This research is an event study within observation period of 7 days. Samples of this study are companies with stock split and reverse stock split during January 2009 - October 2017. The sampling method used is non-probability purposive sampling. Data analysis techniques used to test the hypothesis are wilcoxon signed ranks test and mann-whitney u test. The results show that stock split and reverse stock split obtain reaction from the market as measured by abnormal return. While research on trading volume activity shows there is no increase in average trading volume activity after stock split event and there is no decrease in average trading volume activity after reverse stock split event. This study finds different market reaction between stock split and reverse stock split events.